Molecular identification of mosquito species in the Anopheles annularis group in southern Asia - Walton C. (2014)
The Anopheles annularis group of subgenus Cellia Theobald (Diptera: Culicidae) includes five currently recognized species in southern Asia: An. annularis Van der Wulp, Anopheles nivipes (Theobald) and Anopheles philippinensis Ludlow, which are widespread in the region, Anopheles pallidus Theobald, which is known in Sri Lanka, India and Myanmar, and Anopheles schueffneri Stanton, which occurs in Java and Sumatra. Identification of the four mainland species based on morphology is problematic. In view of the fact that the three widespread species are variously involved in malaria transmission in different parts of the region, we developed a species-specific polymerase chain reaction assay based on rDNA internal transcribed spacer 2 (ITS2) sequences to facilitate entomological and epidemiological studies of the four species. The method proved to be reliable when tested over a wide geographical area. © 2007 The Authors.